PRAGMATIC DIMENSION OF SEMIOTICS IN SONG LYRICS - Pristianingrum, Shinta; Damayanti, Rini (Journal of Pragmatics and Discourse Research, 2022)
This article attempts to reveal the pragmatic dimension of semiotics in the D'MASIV song "Jangan Menyerah". The pragmatic dimension in semiotics relates to the meaning of a sign and how the sign answers questions such as "what for" and "why", and how signs are exchanged and how much value they give to their users. The pragmatic dimension in semiotics is the study of the relationship between signs and their users (interpreters), especially those related to the concrete use of signs in various events (discourse) and their effects or impacts on their users. The semiotic theory used is the opinion of De Saussure. The method in this study uses a qualitative method. While the analysis technique used is the semiotic analysis technique of Ferdinand de Saussure. Saussure's theoretical model focuses more on the signified and the signified. As a result, this research can provide other meanings from the parables explained through Ferdinand De Saussure's theory of semiotic analysis. Every verse of the song "Jangan Menyerah" has meaning and motivation. This study found a motivational message in the song "Jangan Menyerah" to keep fighting under any circumstances, even in a slump, and to always be patient and grateful because God will help.